Evaluation and improvement of rice field quality in Seririt District, Buleleng Regency, Bali Province, Indonesia - Made Sri Sumarniasih; Michael Haganta Ginting; Ida Bagus Putu Bhayunagiri (Journal of Degraded and Mining Lands Management, 2022)
The decline of land quality has an impact on the decline of productivity which in turn reduces production. This kind of thing happened to rice fields in the research area of Seririt District. The objective of this study was to evaluate the rice field quality in Seririt District, Buleleng Regency, Bali Province. The study used a survey method to take soil samples, followed by laboratory analysis for each homogeneous land unit (HLU). The HLU was determined by overlapping soil type maps, slope maps, and utility maps. Parameters analysed were bulk density, texture, porosity, water content, organic C, pH, cation exchange capacity (CEC), base saturation (BS), nutrients (total N, available P, and available K), and biomass C. The results of the laboratory analysis were compared with the criteria for soil quality based on ten minimum data sets (MDS) for each HLU. The results showed that the soil quality at the study site is classified as very good in HLU I with a soil quality index (SQI) of 18. This HLU is located in Rangdu and Ringdikit villages, with an area of 125.15 ha. Good SQI was observed on HLUs II, III, IV, V, VII, and VIII, respectively, located in Banjar Asem, Lokapaksa, Pangkung Paruk, Bestala, Ume Anyar, Mayong, Joanyar, the SQI value of 22-25 is 2,321.49 ha with the limiting factors of total N, total P, texture, and bulk density. The suggested rice field management plan is the addition of organic, nitrogen, and phosphate fertilisers.